THE CURRENT STATE OF THE PROBLEM OF LIPID PEROXIDATION - Iriskulov, B.U.; Abilov, P.M.; Norboeva, S.A.; Musaev, Kh.A.; Urinov, A.M. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
This article assesses the state of the problem of lipid peroxidation. Free radical processes are highly reactive and are essential components of the normal functioning of cells. Are known radicals of hydrogen peroxide, hydroxyl, superoxide radicals and singlet oxygen. To the formation of a radical anion of oxygen and hydrogen peroxide leads to a “respiratory explosion” (an increase in the consumption of oxygen by neutrophils, macrophages, etc.). In peroxisome oxidases, oxygen is restored to hydrogen peroxide (urotoxicity, glycolate oxidase, L-amino acid oxidase). These radicals and active oxygen species (ROS) have a bactericidal effect.